Providing Nursing Care to someone who is undergoing Covid-19 treatment at the Hospital: Case Report - Andria Pragholapati; Lina Anisa Nasution; Irma Darmawati; Dhika Dharmansyah; Imam Tri Sutrisno (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Covid-19 cases in Indonesia are still increasing. Covid-19, both symptomatic and asymptomatic, needs special handling so that the healing process runs with procedures. This case report discusses a patient who was confirmed positive for Covid-19 at the hospital after undergoing 14 days of self-isolation at home. The patient was admitted because the CT value did not change from the first day to the 14th day and after taking the X-ray the results showed pneumonia. The patient was asymptomatic but had high blood pressure at the time of examination at the hospital. This case report discusses nursing care in this patient.